Análise das células intersticiais de cajal e de mastócitos no esôfago de pacientes chagásicos - Patricia Rocha Martins (2011)
Chagas disease is caused by the intracellular parasite Trypanosoma cruzi. In the chronic phase, some patients may develop symptoms with cardiac, digestive or cardiodigestive involvement. Chagasic megaesophagus is one of the most common complications of the digestive form of the disease characterized by disturbances in motility and increase of the esophagus diameter. The main histological changes observed are hyperplasia and hypertrophy of the tunica muscular and degeneration of the enteric nervous system (ENS), associated with an inflammatory process. In this context, we hypothesized that the interstitial cells of Cajal (ICC) and mast cells could contribute for the development of the chagasic megaesophagus. The objectives of this study were to analyze the distribution of ICC and the number of mast cells tryptase-immunoreactive (IR) and mast cells chymase- IR in the muscle layers and myenteric plexus of the esophagus from chagasic patients with and without megaesophagus and noninfected individuals, through immunohistochemical techniques. Furthermore, we proposed to verify the correlation between these cells and innervation of the muscle layers. The results demonstrated that chagasic patients without megaesophagus presented a decrease of the ICC-c-kit- IR area in the muscle layers and an increase in the number of tryptase-IR and chymase-IR mast cells in the muscle layers and myenteric plexus. On the other hand, chagasic patients with megaesophagus showed a decrease of the ICC-c-kit-IR area and an increase in the number of mast cells tryptase-IR in the muscle layers and myenteric plexus. The correlation between ICC-c-kit-IR and nerve fibers PGP 9.5-IR was positive in the muscle layers, as well as, between ICC-c-kit-IR and mast cells chymase-IR in the myenteric plexus. However, the correlation between nerve fibers PGP 9.5-IR and mast cells tryptase-IR was negative. These results suggest that changes in the profile or the number of mast cells tryptase-IR / chymase-IR might contribute to the decrease in the ICC-c-kit-IR area and density of the nerve fibers PGP 9.5-IR, consequently leading to the development of the chagasic megaesophagus